Evaluating task-based brain network activity in pediatric subjects with an mTBI: mechanisms of functional compensation are symptom-level dependent - Holmes, Scott A; Singh-Saluja, Rajeet; Chen, Jen-Kai; Gagnon, Isabelle; Ptito, Alain (Brain injury, 2019)
The diagnosis of a mild traumatic brain injury (mTBI) places large emphasis on patient-reported symptoms which has restricted our ability to evaluate patients. Task-based functional magnetic resonance imaging has the potential to act as an objective measurement of abnormal brain activity and inform clinical decision-making; however, there is little research evaluating pediatric subjects as a function of mTBI-related symptoms. The objective of this study was to evaluate the extent to which brain activity during a spatial navigation task is different between children with mTBI and a group of healthy controls (HCs) based on symptom reporting. A group of patients with mTBI (n = 27) were divided into low- and high-symptom cohorts and compared with HCs (n = 27) on a task that required participants to locate specific landmarks. No difference was found in the level of symptoms reported between patients with low-symptom participants and HCs despite the low-symptom group showing increased activity within the frontal and occipital cortices. In participants with high-symptoms, an increase in the number of reported symptoms was found relative to HCs alongside an increase in the number of active brain regions. Findings suggest that persons with an mTBI may display unique symptom-dependent patterns of altered task-related brain activity.